Outcome analysis of low pressure versus high pressure pneumoperitoneum laparoscopic cholecystectomy: a randomized clinical study - Mahajan, Salil; Shankar, Manu; Garg, Vinod K.; Gupta, Vijender; Sorout, Jaya (International Surgery Journal, 2017)
Background: Laparoscopic cholecystectomy is established as gold standard for management of cholelithiasis. Intraoperative pneumoperitoneum affects the postoperative outcomes. The current stress is on increasing patient safety. Hence, this prospective study was undertaken to compare the effect of low pressure pneumoperitoneum (LPP <10 mm Hg) versus high pressure pneumoperitoneum (HPP > 14 mm Hg) on postoperative pain and ileus. Methods: 120 patients undergoing laparoscopic cholecystectomy were randomized into the LPP (<10mm Hg) group (n=60) and the HPP (>14 mm Hg) group (n=60). Total duration of surgery, intra-operative gas consumption, occurrence of bile spillage during operation, shoulder pain and abdominal pain in postoperative period, additional requirement of analgesia in postoperative period and postoperative ileus were assessed. Results: There was no significant difference in terms of operative duration, consumption of CO2 gas, intraoperative bile spillage, total hospital stay and tolerance to early feeding. The incidence of shoulder pain was higher in patients who underwent HPP laparoscopic cholecystectomy (p<0.05). There was early recovery and early return of bowel activity in LPP which was statistically significant. Conclusions: Low-pressure pneumoperitoneum is feasible and safe and results in reduced postoperative shoulder tip pain and near-equal operative time with early return of bowel activity compared with high-pressure pneumoperitoneum.